Gabriele Fallopio (1523-1562). - Kutya, S. A. (Морфологія / Morphologia / Morfologìâ, 2012)
450 years ago (October 9, 1562), the outstanding Italian anatomist Gabrielle Fallopio (Latininus Fallopius) (Fig.1) died, whom the great French naturalist Georges Cuvier (1769-1832) considered the founder of scientific anatomy along with Andrei Vesalius (1514-1564) and Bartolomeo Eustachio (about 1510-1574).